2019
DOI: 10.1002/adhm.201900968
|View full text |Cite
|
Sign up to set email alerts
|

Models of the Gut for Analyzing the Impact of Food and Drugs

Abstract: The human intestine is the primary organ responsible for the uptake of nutrients and water, and this is facilitated by its complex structure that features a large surface area. With an average total length of around seven meters, including both small and large intestine, it connects the stomach to the rectum while enabling absorption in a specialized manner. At a cellular level, the gut epithelium is critical in selective transport to the bloodstream. The finger-like projections of the intestinal epithelium Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 242 publications
(189 reference statements)
0
31
0
Order By: Relevance
“…11 Although these models are relevant and pertinent to the field of intestinal inflammation modeling, they lack the robustness or relationship to industryadopted cellular standards and are generally not suitable for screening large libraries of compounds. 15 Previously, we introduced an intestinal model comprising perfused tubules composed of the intestinal cell line Caco-2 in a microfluidic platform, the OrganoPlate. 16 The gut tubules showed accelerated cellular polarization, fundamental receptor expression, and tight junction formation in a robust and reproducible manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Although these models are relevant and pertinent to the field of intestinal inflammation modeling, they lack the robustness or relationship to industryadopted cellular standards and are generally not suitable for screening large libraries of compounds. 15 Previously, we introduced an intestinal model comprising perfused tubules composed of the intestinal cell line Caco-2 in a microfluidic platform, the OrganoPlate. 16 The gut tubules showed accelerated cellular polarization, fundamental receptor expression, and tight junction formation in a robust and reproducible manner.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Although these models are relevant and pertinent to the field of intestinal inflammation modeling, they lack the robustness or relationship to industry-adopted cellular standards and are generally not suitable for screening large libraries of compounds. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kim et al implemented key characteristics of intestinal inflammation diseases, including destruction of intestinal villi and associated compromise of the permeability barrier [43]. These damages are believed to origin from interplays between the intestinal epithelium, gut microbes and immune cells and changes in luminal flow due to altered peristalsis [44,45] The developed in vitro human gut-on-a-chip microfluidic device could potentially be further developed to work in a patient specific manner to advance personalized medicine in the futurepassive OIMs can play a key-role in developing personalized medicine and can be tested in these gut-on-a-chip systems as well [46,47,48] For instance, Workman et al demonstrated induced pluripotent stem cells (iPSCs) derived intestinal organoids to express intestine markers (post-14 days differentiation), and their association with IBD was studied upon exposure to the IFN-Îł cytokine [49]. A two-channel PDMS mold was created where cell-monolayer was maintained in the top-channel (1000 ÎŒm high), followed by a thin porous membrane (7 ÎŒm~pore size), and growth media being circulated in the bottom-channel (200 ÎŒm high).…”
Section: Passive Microdevices For Oral Drug Delivery: Opportunities Amentioning
confidence: 99%
“…Animal models, including mice, fish, and insects, have been extensively used to analyze host-microbiome interactions and their contributions to pathophysiology in infectious diseases regarding diet. Mice are the model of choice for most studies in this emerging field, allowing for manipulations in the gut microbiota and host to be studied in a controlled experimental setup [32]. Manipulations include host genetic background manipulation (gene knockouts); gut microbiota composition manipulation (controlled inoculation in germ-free or gnotobiotic mice, i.e., germ-free mice administered with human microbes); and ecosystem interventions, including dietary interventions, antibiotic treatment, and fecal transplantations.…”
Section: Limitations Of Traditional In Vivo and In Vitro Modelsmentioning
confidence: 99%